Foreign direct investment and intra-industry spillovers: a review of the literature - Holger Görg; David Greenaway (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
Many governments offer significant inducements to attract inward investment, motivated by the expectation of spillover benefits. This paper reviews the possible sources of such spillovers and the empirical evidence for their existence in developing, developed and transitional economies. Although theory can identify a range of possible spillover channels, empirical support is hard to find. In the light of this, the paper concludes with a review of policy aspects.
Keywords: 330; Direktinvestition; Investitionspolitik; Spillover-Effekt; Intraindustrieller Handel; Agglomerationseffekt; Theorie